Assessing the Impact of Dividend Policies on the Market Valuation of Development Banks in Nepal - Dongol, Padam; Shrestha, Anuj (Journal of Kathmandu BernHardt College, 2023)
This research delved into the assessing the impact of dividend policies on the market valuation of development banks in Nepal. Employing a cross-survey methodology, the study utilized data from secondary sources, specifically the annual reports of various development banks. The sample for the study included four national development banks, covering the time span from 2014/15 to 2020/21. Both descriptive and inferential statistical techniques were applied in analyzing the data. The dependent variable in this research was the market price, with independent variables including the price-earnings ratio, dividends, and earnings. The results indicated that price-to-earnings ratios and earnings per share exerted a positive and significant influence on the market price. Conversely, dividends per share showed no impact. Consequently, the market price movement is not consistently determined by the dividends paid out by the company.